PENINGKATAN PROFESIONALISME GURU MELALUI WORKSHOP MEMBUAT INDIKATOR PENCAPAIAN KOMPETENSI KURIKULUM 2013 BAGI GURU PENDIDIKAN AGAMA HINDU TINGKAT SMA/K DI KABUPATEN BANGLI SEMESTER GANJIL TAHUN PELAJARAN 2018/2019 - Wandri, I Nyoman (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The aims of this study is to improve the teacher professionalism through workshops to make an indicator of the achievement of 2013 curriculum competencies for teachers of Hindu religious education at senior high school in Bangli Regency. This study was a School Action Research (PTS) which using three cycles design and each cycle consists of four stages, namely: planning, action, observation, and reflection. A measurement technique in the form of test is used to obtain a quantitative data, and an observation sheet is used to presented the qualitative data. The data was analyzed by using descriptive analysis. Furthermore, based on the results of this study, first at the end of the first cycle the increase of the average professionalism of teachers through workshops made the 2013 Curriculum Competency Achievement Indicator from the previous training was 64.22 to 73.4. Then, after the third cycle the professional level of teachers made the 2013 Curriculum Competency Achievement Indicator become 78.94 reaches the predicate of good value. Second, it turned out that the increase of the teacher professionalism through workshops made the Indicator of 2013 Curriculum Competency Achievement for Hinduism teachers at Senior High School in Bangli Regency in the academic year 2018/2019 shows very significant results from the initial conditions before receiving the training.